2002
DOI: 10.1001/jama.287.7.863
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Inhalational Anthrax in a 94-Year-Old Connecticut Woman

Abstract: We describe the 11th case of bioterrorism-related inhalational anthrax reported in the United States. The presenting clinical features of this 94-year-old woman were subtle and nondistinctive. The diagnosis was recognized because blood cultures were obtained prior to administration of antibiotics, emphasizing the importance of this diagnostic test in evaluating ill patients who have been exposed to Bacillus anthracis. The patient's clinical course was characterized by progression of respiratory insufficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 14 publications
4
97
0
2
Order By: Relevance
“…53,54 The drug rFVIII may enable enhancing coagulation in patients with anthrax who exhibit severe hemorrhage and coagulopathy, as described in clinical settings. [9][10][11][12]31 To develop an effective treatment against anthrax, combining other anti-anthrax agents with a coagulation intervention strategy may be a feasible approach. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 The drug rFVIII may enable enhancing coagulation in patients with anthrax who exhibit severe hemorrhage and coagulopathy, as described in clinical settings. [9][10][11][12]31 To develop an effective treatment against anthrax, combining other anti-anthrax agents with a coagulation intervention strategy may be a feasible approach. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the reason both clinical and animal studies have revealed that hemorrhagic disorder is one of the major manifestations of LT-treated or B. anthracis-infected hosts remains unclear. [7][8][9][10][11][12][13] Recent studies have shown that LT might contribute to hemorrhage by inducing thrombocytopenia and megakaryocytic suppression. [14][15][16] The mechanism underlying coagulation suppression, however, remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of both inhalational and cutaneous anthrax cases clearly exemplifies these roles. 6,7,60,61 In addition to B. anthracis, several rapid and sensitive IHC assays have been developed for detecting other bioterrorism-related agents, such as Ebola virus, 62,63 Fransicella tularensis, 64 Yersinia pestis, 65 and smallpox virus. These assays provide a method for rapid diagnosis and have fortified the preparedness of responses to possible bioterrorism events.…”
Section: Discussionmentioning
confidence: 99%
“…Fulminant victims receiving critical care would be rescued based on the survival rate (58.3%) of recent inhalational anthrax cases. [36][37][38] Rescued ICU victims would then receive 10 days of non-ICU inpatient care.…”
Section: Kyriacou Et Almentioning
confidence: 99%